Effect of catalytic and energy supplementation on kid performances grazing natural rangelands in north-west Tunisia - Ammar H.; Kamoun M.; López S. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
The effect of multi-nutrient blocks and energy concentrates supply on the performance of growing kids grazing natural rangelands in North-West Tunisia was investigated. Forty kids (average initial weight 13.8 ± 0.38 kg) of a local goat Tunisian breed were used. The trial included an adaptation period (1 month) to the intake of the shrubs in the natural rangeland and an experimental period (45 days). Kids were arranged in four groups each with 10 animals, and the four experimental treatments were allocated according to a completely randomised design. Experimental treatments were control (C) with kids browsing in the rangeland with no supplementation; kids receiving during the night a multi-nutrient block (with urea, molasses, vitamins and minerals) ad libitum (catalytic supplementation, CS); kids supplemented with 300 g barley (energy supplementation, ES); and kids supplemented with both multi-nutrient block and 300 g barley (CES). Kids were weighed three times through the experimental period. As compared with control group, average daily weight gain (ADG) was higher (P < 0.001) in animals receiving catalytic supplementation (94 ± 10.6 g/d vs 40 ± 5.6 g/d, for CS and C animals, respectively). The ADG was increased in kids receiving energetic supplementation (129 ± 6.6 g/d) in comparison with groups C (P < 0.001) and CS (P = 0.005), and growth was further improved by the combined supplementation with multi-nutrient blocks and barley (P < 0.001 for CS vs CES; P = 0.003 for CE vs CES), with animals in CES group reaching ADG of 166 ± 9.4 g/d. Catalytic and energy supplementation enhanced performance of growing kids browsing shrubby vegetation, and the inclusion of both supplements resulted in a synergic outcome.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)